Pengaruh Perputaran Piutang Terhadap Arus Kas Dan Profitabilitas Perusahaan Sawit Pada Tahun 2021-2022 - Sari, Ajeng Kartika; Agustina, Rachma (Prodi Akuntansi, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
This research aims to determine whether there is an influence of receivables turnover on the cash flow and profitability of palm oil companies listed on the IDX for the 2021-2022 period. The data collection technique used in this research was purposeful sampling and a sample size of 42 palm oil companies registered on the IDX for 2021-2022 was obtained. Data analysis used the SPSS version 25 software method. The results of this research show that: (1) Receivables turnover has no effect on cash flow. (2) Receivables turnover has no effect on profitability.